Mandibular Molar Distalization with Jones Jig Appliance - Oktay Üner; Seda Haydar (Galenos Yayinevi, 1999)
Jones Jig appliance has been used in upper first molar distalization . The purpose of this study was to evaluate the effects of Jones Jig appliance on mandibular first molars and dentofacial structures . The sample consisted of 30 patients between 9-13 years of age with class III dental relationship and a discrepancy on one side of mandibular arch . 15 patients were selected as the treatment group and 15 patients served as the control group . Jones Jig appliance was used for molar distalization in the treatment group for an average period of 2.4 months. Angular and linear 37 parameters were selected and "Wilcoxon" and "Mann Whitney U " tests were performed to evaluate the differences between the treatment and control groups . Also Spearman correlation test was used to evaluate the correlations between molar distalization and the dento-skeletal parameters which changed significantly during treatment. Jones Jig appliance obtained 1.9 mm molar distalization .In addition, it prevented 1mm of molar mesialization which was observed in the control group and also ituprighted the mandibular first molars 7 degrees in 2.4 months. During molar distalization protrusion of lower incisors was observed but the lower lip position was not affected Mesial tipping of lower bicuspids and a decrease in overbite and overjet was observed in the treatment group.Anterior ör posterior mandibular rotation was not evident and no relationship could be found between the molar distalization and the dento-skeletal parameters which significantly changed during the treatment.